Biologics in juvenile idiopathic arthritis-main advantages and major challenges: A narrative review - Amra ADROVIC; Mehmet YILDIZ; Oya KÖKER; Sezgin ŞAHİN and Kenan BARUT and Özgür KASAPÇOPUR (Archives of Rheumatology, 2021)
Juvenile idiopathic arthritis (JIA) is the most common rheumatic disease in childhood. The disease is divided in different subtypes based on main clinical features and disease course. Emergence of biological agents targeting specific pro-inflammatory cytokines responsible for the disease pathogenesis represents the revolution in the JIA treatment. Discovery and widespread usage of biological agents have led to significant improvement in JIA patients’ treatment, with evidently increased functionality and decreased disease sequel. Increased risk of infections remains the main discussion topic for years. Despite the slightly increased frequency of upper respiratory tract infections reported in some studies, the general safety of drugs is acceptable with rare reports of severe adverse effects (SAEs). Tuberculosis (TBC) represents the important threat in regions with increased TBC prevalence. Therefore, routine screening for TBC should not be neglected when prescribing and during the follow-up of biological treatment. Malignancy represents a hypothetical complication that sometimes causes hesitations for physicians and patients in its prescription and usage. On the other hand, current reports from the literature do not support the increased risk for malignancy among JIA patients treated with biological agents. A multidisciplinary approach including a pediatric rheumatologist and an infectious disease specialist is mandatory in the follow- up of JIA patients. Although the efficacy and safety of biological agents have been proven in different studies, there is still a need for long-term, multicentric evaluation providing relevant data.